Formation of carbides by electro-discharge machining of alpha iron - Cabanillas, Edgardo Domingo (2000)
The surface of pure iron sheets have been submitted to spark-planing erosion using kerosene as dielectric under a wide range of machining conditions: discharge duration times between 2 and 3072 μs, and spark currents between 3.3 and 25 A. The carbides formed by the electro-discharge machining process have been identified by X-ray diffraction and Mössbauer spectroscopy. Two different regimes of carbide formation were established: for sparks of energy below ≈0.5 J only ε-carbide, austenite and martensite were observed; for sparks of higher energy mainly cementite, austenite and traces of martensite, Fe7C3, or Fe5C2 were detected.